Analisis Kesesuaian Lahan Bekas Tambang Batubara pada PT Asia Multi Invesama di Kabupaten Tebo Provinsi Jambi - Shilvyanora Aprilia Rande (PROMINE, 2016)
Every activity mining always pertaining to the environment so that are obliged to apply rules miningtechnique good, among others to carry out the management and environmental monitoring miningincluding reclamation activities. The environment quality will go down caused by clearing land so as tointerfere with ecosystem that is in them. The administration land done PT AMI are stockpiling backholes former mine done by means of back filling and stockpiling by means of the material heaps atwaste dump area. The condition design waste dump is still considered not yet safe especially the formof heap and arrangement layers material heap of which are not based on to the level of his layers.Activities revegetation PT AMI undertaken by those species of plants and mahogany trembesi not inaccordance with the hue early research sites and land use in spatial planning Kabupaten Tebo. Basedon the evaluation of conformity and management of land that in order to land a former mine is aimedmore compatible by doing revegetasi in the form of a kind of the rubber plant. In reaching the level ofsuccess revegetasi, needs to be planting cover crop and weed control so that plants can grow well.